P90 Steroid dose reduction and weight loss in patients with severe asthma who respond to mepolizumab. (12th November 2019) - Thomas, N; Hama, B; Elsey, L; Ustabasi, C; Maguire, L; Fowler, S; Pantin, T; Allen, D; Tavernier, G; Niven, R
Abstract : Background: Mepolizumab, a human monoclonal antibody, blocks interleukin-5, a major contributor to airway inflammation in eosinophilic asthma. Mepolizumab has been shown to reduce exacerbations rate and steroid burden in severe asthma. Existing patients first started treatment 2 years ago and here we report outcome data for patients with severe asthma commenced on 100 mg subcutaneously every 4-weeks for a minimum of 6 months. Methods: Data from patients completing at least 6 months of treatment with mepolizumab are reported. 'Responders' were defined as having at least a 50% reduction in their daily steroid dose at 12 months. Each variable measured was checked for normality of distribution and longitudinal changes were analysed using paired sample tests accordingly, t-tests for parametric data and Wilcoxon tests for non-parametric data. Results: Patients with severe adult asthma were included (n=194), 64.9% female, mean (SD) age 51.09 (12.13) yrs, FEV1 (n=159) 64.45 (21.63)% predicted, baseline daily dose (n=182) 10 (0–60)mg oral prednisolone. 74% (n=85) of patients were identified as responders, (though this figure does not include patients who did not reach 6 months of treatment). Of the patients who had sputum samples taken at 12 months, 15% (n=2) of responders (n=13) and 62% (n=5) of non-responders (n=8) were sputum eosinophil positive. All of these paired sample tests for AQLQ, ACQ, blood eosinophils, oral corticosteroids and weight show improvement with clinical significance of P<0.01. Prednisolone dose decreased by a mean of 10 mg in responders and weight decreased by 7 kg. FeNO increased only in non-responders by a mean of 12ppb and there was no change in FEV1 . Conclusions: As well as a significant reduction in mean oral corticosteroid dose and patient weight, sputum eosinophilia was strongly associated with clinical response and may be useful at predicting those who are not responsive at 6 months and may need to switch to a second-line biologic agent.